Professionalism and Pesticides: Public and Customer Communications - Frederick M. Fishel (EDIS)
PI-177, a 4-page illustrated fact sheet by Frederick M. Fishel, describes the components of professionalism, how to talk to customers about pesticides, notification requirements, and recordkeeping. Includes additional sources of information. Published by the UF Department of Agronomy, January 2009.